Investigating a new conservative 4-dimensional chaotic system - Mati ur Rahman; M.A. El-Shorbagy; Hussam Alrabaiah; Dumitru Baleanu; Manuel De la Sen (Results in Physics, 2023)
This study analyzed a modified conservative 4D chaotic system is investigated using both integer and non-integer order derivatives. Several dynamical aspects of the said model are explored, such as stable equilibrium points, Lyapunov spectra (LS), attractor projection, Poincare, bifurcations and phase portrait. The system is also analyzed using a singular fractional operator, and the theory of the existence of solutions is established through functional analysis. To obtain numerical results of the fractional order system, a numerical method based on Newton polynomial is applied. The study reveals the presence of hidden and fixed point chaotic attractors for certain fractional order values.